Facing global economic crisis: Foreign sales, ownership groups, and corporate value - MA, Xufei (Institutional Knowledge at Singapore Management University, 2014)
This study extends the research on internationalization to a new organizational context emerging market firms (EMF), and a new time context global economic crisis. We propose a U-shaped relationship between foreign sales intensity and firm value for EMFs during global economic crisis. Further, we distinguish between EMFs' relational owners (i.e., business groups) and transactional owners (i.e., institutional investors) to investigate their different moderating effects. We find empirical support for our hypotheses using a sample of Chinese firms during the global economic crisis in 2008. Moreover, we provide research and practice implications.